2020
DOI: 10.1186/s13756-020-00782-x
|View full text |Cite|
|
Sign up to set email alerts
|

High rate of extended-spectrum beta-lactamase-producing gram-negative infections and associated mortality in Ethiopia: a systematic review and meta-analysis

Abstract: Background: Extended-spectrum beta-lactamase (ESBL)-producing Gram-negative bacteria have become a serious threat to global health. Their rapid spread is associated with high mortality due to ineffective antibiotic treatment. To date a regular surveillance of multidrug-resistant (MDR) pathogens in Ethiopia is not established. For this report, published data regarding ESBL-producing bacteria in different health facilities of Ethiopia were reviewed. Methods: This study collates data from published information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Although advances have been made in our understanding of the epidemiology of these organisms in high-income countries ( Han et al, 2017 ;Han et al, 2012 ;Lautenbach et al, 2012 ;Sheu et al, 2018 ), few data exist from low and middle-income countries (LMICs). Studies that have been conducted in LMICs have been limited because of inconsistent identification and susceptibility testing, reliance on only clinical specimens, and a primary focus on the hospital setting ( Andrew et al, 2017 ;Bulabula et al, 2017 ;Saravanan et al, 2018 ;Singh-Moodley and Perovic, 2016 ;Sonda et al, 2016 ;Tufa et al, 2020 ;Workneh et al, 2017 ). In addition, most previously published research data has been focused on healthcare-associated infections (HAIs), and there are minimal data on colonization by ESCrE and CRE within individuals in community and healthcare settings ( Andrew et al, 2017 ;Saravanan et al, 2018 ;Singh-Moodley and Perovic, 2016 ;Tufa et al, 2020 ;Workneh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although advances have been made in our understanding of the epidemiology of these organisms in high-income countries ( Han et al, 2017 ;Han et al, 2012 ;Lautenbach et al, 2012 ;Sheu et al, 2018 ), few data exist from low and middle-income countries (LMICs). Studies that have been conducted in LMICs have been limited because of inconsistent identification and susceptibility testing, reliance on only clinical specimens, and a primary focus on the hospital setting ( Andrew et al, 2017 ;Bulabula et al, 2017 ;Saravanan et al, 2018 ;Singh-Moodley and Perovic, 2016 ;Sonda et al, 2016 ;Tufa et al, 2020 ;Workneh et al, 2017 ). In addition, most previously published research data has been focused on healthcare-associated infections (HAIs), and there are minimal data on colonization by ESCrE and CRE within individuals in community and healthcare settings ( Andrew et al, 2017 ;Saravanan et al, 2018 ;Singh-Moodley and Perovic, 2016 ;Tufa et al, 2020 ;Workneh et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have been conducted in LMICs have been limited because of inconsistent identification and susceptibility testing, reliance on only clinical specimens, and a primary focus on the hospital setting ( Andrew et al, 2017 ;Bulabula et al, 2017 ;Saravanan et al, 2018 ;Singh-Moodley and Perovic, 2016 ;Sonda et al, 2016 ;Tufa et al, 2020 ;Workneh et al, 2017 ). In addition, most previously published research data has been focused on healthcare-associated infections (HAIs), and there are minimal data on colonization by ESCrE and CRE within individuals in community and healthcare settings ( Andrew et al, 2017 ;Saravanan et al, 2018 ;Singh-Moodley and Perovic, 2016 ;Tufa et al, 2020 ;Workneh et al, 2017 ). Colonization is typically a prerequisite for infection and an important stage in pathogenesis ( Emmanuel Martinez et al, 2019 ;Massart et al, 2020 ;McConville et al, 2017 ;Reddy et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom, the mortality rate from bacteraemia infection caused by ESBL-producing E. coli was 60.9% as against 27.3% from those that did not produce ESBL. 8 In their systematic review and meta-analysis in Ethiopia, Tufa et al 9 reported a death rate of 33.3% and 100.0% due to infections caused by ESBL-producing gram-negative isolates in two separate studies. Infection with ESBL-producing organisms is severe in developing countries like Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Kentucky has led to the identification of several different STs; these involve strains containing a range of genes that confer resistance to multiple drugs (Haley et al, 2017). Cephalosporin antibiotics play an important role in the treatment of clinical patient infections and the main mechanisms of cephalosporins resistance in Salmonella are mediated by extended-spectrum beta-lactamases (ESBL) genes (Bae et al, 2015;Tufa et al, 2020). The Salmonella genomic island 1 (SGI1) refers to a gene cluster with typical characteristics on the bacterial chromosome, which carries multiple drug-resistance genes and determines the multidrug resistance of the bacteria (Carraro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%